Stare Decisis -doctrine and trust in the Supreme Court: Has something changed? - Kangasluoma, Leevi (My University, 2024)
My bachelor’s thesis is about the decision-making and more specifically, the stare decisis -doctrine in the Supreme Court. I will examine three overruling cases and their overruled precedents in order to find similarities and, on the other hand, differences between the stare decisis -doctrines of these cases. The overruling cases are Dobbs, Brown and Barnette. Doing this, I expect to gain a better understanding between the balance of rule of law and ideologies and politics in the decision-making of the Supreme Court in the United States. First, I will analyse the arguments that the Supreme Court used in the Dobbs case, where Roe and Casey were overruled. Then I will compare those arguments with ones used in Brown and Barnette. My main research method is obviously case argumentation analysis, so my basic idea is to, in a way, put these three overruling cases next to each other and compare them. In this regard, I will also analyse whether the current composition of the Supreme Court is more inclined to overturn its own precedents than its precursors and how it seems to treat the stare decisis -doctrine. After this, I will try to find reasons for Americans’ historically low confidence in Supreme Court. Then I will present a few possible means to make Americans trust the Supreme Court again. Lastly, I will come to my conclusion of this research and analyse where the conclusion leaves us.

Notaarityöni käsittelee Yhdysvaltain korkeimman oikeuden päätöksentekoa ja erityisesti stare decisis -doktriinin soveltamista. Tarkastelen kolmea tapausta, joissa korkein oikeus on kumonnut ennakkotapauksiaan, löytääkseni kumoamisista samankaltaisuuksia ja eroavaisuuksia sovelletussa stare decisis -doktriinissa. Kumoavat tapaukset ovat Dobbs, Brown ja Barnette. Tarkastelemalla tapauksia pyrin saamaan paremman ymmärryksen laillisuusperiaatteen ja ideologioiden ja politiikan tasapainosta Yhdysvaltain korkeimman oikeuden päätöksenteossa. Aloitan analysoimalla argumentaatiota, jota oikeus käytti Dobbsin tapauksessa, jossa Roe ja Casey kumottiin. Sen jälkeen vertaan näitä argumentteja Brownissa ja Barnettessa käytettyihin argumentteihin. Päätutkimusmetodini on tapauksen argumentation analysointi, ja perusideanani on verrata aiemmin mainitsemiani kolmea kumoavaa tapausta toisiinsa. Aiheeseen liittyen, aion myös tutkia, onko korkeimman oikeuden nykyinen tuomarikokoonpano edeltäjiään taipuvaisempi kumoamaan ennakkotapauksia, ja kuinka se käsittelee stare decisis -doktriinia. Tämän jälkeen pyrin löytämään syitä yhdysvaltalaisten historiallisen alhaiseen luottamukseen korkeinta oikeutta kohtaan. Sitten esitän muutaman keinon, joilla luottamus voitaisiin mahdollisesti palauttaa. Lopuksi kerron tutkitelmani johtopäätöksistä ja mietin, mikä niiden merkitys on.
Keywords: stare decisis, Supreme Court, Dobbs, Roe v. Wade, Casey, Brown, Plessy, Barnette, Gobitis, precedent, overruling, legitimacy, confidence in Supreme Court, rule of law, Bush v. Gore, decision-making, argumentation, Yhdysvaltain korkein oikeus, ennakkotapaus, kumoaminen, legitimiteetti, luottamus korkeimpaan oikeuteen, laillisuusperiaate, päätöksenteko, argumentaatio